Tunneling and quantum localization in chaos‐driven symmetric triple well potential: An approach using quantum theory of motion. Issue 10 (3rd November 2017) - Kar, Susmita; Chattaraj, Pratim Kumar
Abstract: For a symmetric triple well potential, driven by the forces associated with the bifurcation diagram of a logistic map, the tunneling and quantum localization are studied using quantum theory of motion and time‐dependent Fourier grid Hamiltonian methods. Detailed analysis reveals that application of only asymmetric or symmetric perturbation results into either quantum localization or over‐barrier transition and no tunneling while application of mixed symmetry perturbation gives either tunneling or over‐barrier transition, depending on temporal nature and initial position of the particle. For bifurcative and chaotic symmetric‐asymmetric perturbation, with truncation of mixed symmetry perturbation, a sudden jump in energy causes a transition from the tunneling phenomenon to the over‐barrier transition. With particle located initially near to either of the minima of the unperturbed well, quantum localization, or over‐barrier transition is observed, depending on types of perturbation used. Abstract : Tunneling and quantum localization dynamics of a particle placed in a chaos‐driven symmetric triple well potential can be understood in terms of quantum theory of motion. Application of a mixed symmetry perturbation leads to tunneling or over‐barrier transition depending on the temporal nature of the applied force and initial position of the particle. On the other end, only asymmetric or symmetric perturbation leads to quantum localization or delocalization via over‐barrier crossing.